The Study of Self-Awareness and Academic Achievement of On-Probation Undergraduate Students by Using U-ARE Self-Awareness Program - Teerasantikul, Pakpoom; Janyam, Kanda; Laeheem, Kasetchai (Migration Letters, 2023)
The purposes of this research were to compare the self-awareness and academic achievement of on-probation undergraduate students before and after receiving the U-ARE Self-Awareness Program and to compare the self-awareness and academic achievement of on-probation undergraduate students between the experimental group receiving the U-ARE Self-Awareness Program and the control group receiving self-awareness information. The sample group in this research were 40 on-probation undergraduate students or equivalent in the academic year 2021 in Prince of Songkla University, Hat Yai Campus who were enrolled and studying at Prince of Songkla University, Hat Yai Campus in the first semester of the academic year 2022. They were obtained by using the stratified-random sampling method and divided into two groups: an experimental group of 20 students and a control group of 20 students. The research tools were 1) U-ARE Self-Awareness Program in the form of 10 group activities, 2) information about self-awareness, 3) a self-awareness scale of 60 items of which the concordance (IOC) was between .80-1.00 and the confidence was equal to 0.86, and 4) student academic achievement results. The statistics used to analyze the data were mean, standard deviation and one-way multiple analysis of variance using Hotelling T2 statistics. The results showed that the students receiving the U-ARE Self-Awareness Program had a higher level of self-awareness and academic achievement after the experiment than before the experiment at the .05 level of significance. In addition, the students receiving the U-ARE Self-Awareness Program had a higher level of self-awareness and academic achievement after the experiment than that of those receiving information about self-awareness at the .05 level of significance.